Correlation between PAI Teacher's Teaching Style and Student Learning Interest - Arrozi, Fatahillah; Kholifaturrahmah , Nurul (Tsaqofah : Jurnal Pendidikan Islam, 2021)
This study aims to determine whether there is a relationship between teaching style and student learning interest . The method used is quantitative research which is correlational. The sampling technique in this study used Simple Random Sampling, which is a total of 30 respondents from 137 students at SMK Negeri 1 Grujugan Bondowoso. The hypothesis test was carried out with the help of Statistical Package for the science (SPSS) software version 24. From the analysis and research obtained, it shows that the correlation between the teaching style of PAI teachers and student interest in learning is 0.583 while the rtable at a significant level of 5% is 0.361. And from these results it can be seen that rcount 0.583 is greater than rtable 0.361. Thus, it can be concluded that there is a significant and positive relationship between the teaching style of PAI teachers and students' interest in learning, and with a moderate correlation coefficient level.